The Effect of Light Color of Lamp on Bagan Tancap Catching Equipment on Catches in the Waters of Sadai Village South Bangka Regency - Gunawan, Irvan; Lisna, Lisna; Ramadhan, Fauzan; Filawati, Filawati; Nelwida, Nelwida; Nurhayati, Nurhayati (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
Fishermen in the waters of Sadai Village mostly use the Bagan tancap by catching using different colors of lights. The study aimed to determine the effect of light colors (white, red, yellow, green, and blue) on the Bagan tancap fishing gear on catches in the waters of Sadai Village, South Bangka Regency. This research was conducted on April 28 - May 28 2022 in the waters of Sadai Village, South Bangka Regency. The method used is an experimental method using a randomized block design (RBD) and Duncan's further test. The data collected includes the type of catch, the total weight of the catch, the number of catches, and environmental parameters. The results showed that the treatment of different light colors affected the number (fish) and weight (kg) of the catches on the Bagan tancap. The composition of the catch on the Bagan tancap for the species caught is squid (Loligo sp) and Curvespine cuttlefish (Sepia recurvirostra) which are the main catch (HTU) while Starry triggerfish (Abalistes stellaris), mackerel (Rastrelliger brachysoma), Yellowtail scad (Atule mate), and Doublewhip threadfin bream (Nemipterus nematophorus) are by-catch. Based on the results, it can be concluded that blue light is a good color for catches in the form of number (fish) and weight (kg) on ​​the Bagan tancap fishing gear.